EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF BERBASIS STEM TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA SMP NEGERI 2 PADANGSIDIMPUAN - Harahap, Sinar Depi; Harahap, Muhammad Syahril; Sipahutar, Renita (JURNAL MathEdu (Mathematic Education Journal), 2024)
This research aims to determine the effectiveness of the STEM-based cooperative learning model on students' critical thinking skills in mathematics at SMP Negeri 2 Padangsidimpuan. This type of research is experimental research with a one group pretest posttest design. The sample obtained was 32 students taken using the Calster random sampling technique. Data collection uses observation, and tests of students' mathematical critical thinking abilities that have previously been validated. The data analysis used is descriptive analysis and differential statistics. Based on descriptive analysis, the average score for implementing the STEM-based cooperative learning model is 3.5 (very good category), the average score for students' mathematical critical thinking abilities in spatial material before using the STEM-based cooperative learning model is 56.06 (category less) and the average score after using the STEM-based cooperative learning model is 95.66 (very good category). Furthermore, based on inferential statistics using the paired sample test (SPSS23), a significance value of 0.000 < 0.0 was obtained, so that the alternative hypothesis in this research could be accepted as true. This means that there is a very significant influence between the use of the STEM-based cooperative learning model on students' mathematical critical thinking abilities at SMP Negeri 2 Padangsidimpuan where the average value of the N-gain index is 0.94 (high category).